Impaired fracture healing is associated with callus chondro-osseous junction abnormalities in periostin-null and osteopontin-null mice - Marc Teitelbaum; Marc Teitelbaum; Maya D. Culbertson; Charlene Wetterstrand; J. Patrick O’Connor; J. Patrick O’Connor (Experimental Biology and Medicine)
Periostin and osteopontin are matricellular proteins abundantly expressed in bone fracture callus. Null mutation of either the periostin (Postn) gene or the osteopontin (Spp1) gene can impair bone fracture healing. However, the cell and molecular pathways affected by loss of POSTN or SPP1 which lead to impaired fracture healing are not well understood. To identify potential pathways, a detailed radiological, histological, and immunohistochemical analysis of femur fracture healing in Postn-null (PostnKO), Spp1-null (Spp1KO), and normal (WT) mice was performed. Apparent changes in specific protein levels identified by immunohistochemistry were confirmed by mRNA quantitation. Comparisons between the PostnKO and Spp1KO fracture calluses were confounded by interactions between the two genes; loss of Postn reduced Spp1 expression and loss of Spp1 reduced Postn expression. Consequently, alterations in fracture healing between mice heterozygous for the Postn-null allele (PostnHET) as well as the PostnKO and Spp1KO mice were similar. Calluses from PostnHET, PostnKO, and Spp1KO mice all had dysmorphic chondro-osseous junctions and reduced numbers of osteoclasts. The dysmorphic chondro-osseous junctions in the PostnHET, PostnKO, and Spp1KO calluses were associated with reduced numbers of MMP-13 expressing hypertrophic chondrocytes, consistent with delayed cartilage resolution. Unlike collagen X expressing callus chondrocytes, chondrocytes only expressed MMP-13 when localized to the chondro-osseous junction or after traversing the chondro-osseous junction. Cyclooxygenase-2 (COX-2) expression also appeared to be reduced in osteoclasts from the PostnHET, PostnKO, and Spp1KO calluses, including in those osteoclasts localized at the chondro-osseous junction. The results indicate that POSTN and SPP1 are necessary for normal chondro-osseous junction formation and that signaling from the chondro-osseous junction, possibly from COX-2 expressing osteoclasts, regulates callus vasculogenesis and chondrocyte hypertrophy necessary for endochondral ossification during fracture healing.